Tunneling Incentive, Debt Covenant, dan Nilai Tukar terhadap Transfer Pricing: Moderasi Ukuran Perusahaan - Dian Aprilia Adriani; Nedi Hendri; Ana Septiani (Universitas Muhammadiyah Metro, 2026)
The purpose of this research is to analyze the influence of tunneling incentive, debt covenant, and exchange rate on transfer pricing moderated by company size. This research uses a sample of mining companies listed on the Indonesia Stock Exchange during the years 2021-2023. The number of mining companies that were sampled is 11 companies over 3 (three) years, with a total research sample of 33 financial statements. The method used is purposive sampling. Hypothesis testing in this study uses Structural Equation Modeling (SEM) with the assistance of Partical Least Square (SmartPLS) version 4.0 software. This study shows that tunneling incentive and debt covenant significantly affect the company's decision to engage in transfer pricing, while exchange rate does not affect transfer pricing. Then, the size of the company is able to moderate the tunneling incentive towards transfer pricing. However, the size of the company is unable to moderate the debt covenant and also the exchange rate in the company's decision to engage in transfer pricing.